Modeling Diversity: Do Homogeneous Laboratory Strains Limit Discovery?. Issue 11 (November 2018) - Smith, Clare M.; Sassetti, Christopher M.
Abstract : The outcome of chronic infections is highly variable. The heterogeneous disease outcomes in natural populations differ from genetically homogeneous infection models. Here, we use tuberculosis as a 'case study' to contrast the genetic landscape in natural populations with standard infection models, discussing new strategies to bridge this gap.